Tax Disputes Arising from Value Added Tax Treatment of Foreclosed Collateral Transactions - Sidabutar, Hartini Vera S.H.; Nuryanah, Siti (E-Jurnal Akuntansi; Vol 34 No 9 (2024)DO - 10.24843/EJA.2024.v34.i09.p13, 2024)
This study aims to examine the underlying causes of value-added tax (VAT) disputes related to foreclosed collateral (AYDA). A case study approach was employed, utilizing a triangulation method that combined content and literature analysis with interviews conducted with tax consultants, auditors, and Tax Court judges. The findings indicate a rising trend in VAT disputes concerning AYDA, primarily driven by differences in interpretation between tax authorities and taxpayers. Additionally, inconsistencies between applicable regulations and the nature of taxpayers’ business operations contribute to these disputes. This research provides valuable insights into the factors leading to VAT disputes on AYDA and offers practical implications for reducing such conflicts. By identifying key areas of regulatory misalignment and interpretational discrepancies, the study contributes to the development of more effective tax policies and compliance strategies, ultimately helping to mitigate future disputes.